2010
DOI: 10.5326/0460385
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax: A Review

Abstract: Pneumothorax is a pathological condition in which air accumulates within the thoracic cavity. Pneumothorax affects animals without sex or age predilections; however, it has been suggested that the Siberian husky breed of dog has a predisposition for spontaneous pneumothorax. Pneumothorax occurs as the result of trauma or underlying disease and can present a clinical challenge with regard to diagnostic and therapeutic techniques. Topics reviewed include normal lung physiology; the pathogenesis, diagnosis, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 32 publications
2
50
0
13
Order By: Relevance
“…The poor Se of three‐view thoracic radiology for detecting pneumothorax is consistent with human studies that reported CT being able to detect more than twice the number of pneumothoraxes compared to radiology . The cases missed in our study were most likely due to small amounts of air being trapped between lung lobes and the mediastinum instead of accumulating at the highest point in the thorax.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The poor Se of three‐view thoracic radiology for detecting pneumothorax is consistent with human studies that reported CT being able to detect more than twice the number of pneumothoraxes compared to radiology . The cases missed in our study were most likely due to small amounts of air being trapped between lung lobes and the mediastinum instead of accumulating at the highest point in the thorax.…”
Section: Discussionsupporting
confidence: 81%
“…Although dogs are able to tolerate thoracic expansion by 2.5‐3.5 times the residual volume, it is unknown whether the presence of an undetected pneumothorax is life‐threatening in dogs undergoing general anesthesia or mechanical ventilation . It is thus prudent to monitor ventilation closely for complications where pneumothoraxes are equivocal or absent on thoracic radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate thoracocentesis is both diagnostic and therapeutic. 17 Electrolyte and Acid/Base Imbalances Hyperkalemia, hypocalcemia, and acidosis will decrease myocardial contractility and blood pressure. These problems need to be corrected before blood pressure can be restored.…”
Section: Tension Pneumothoraxmentioning
confidence: 99%
“…[3][4][5] Previously reported etiologies of pneumothorax in dogs include neoplasia, pulmonary abscess, lung parasitism, migrating foreign body, pulmonary thromboembolism, and pneumonia. 6,7 Pneumothorax secondary to thromboembolism in dogs is rare and generally involves chronic underlying processes (eg, Dirofilaria immitis infection and hyperadrenocorticism). 7,8 Necrotizing pneumonia or pneumothorax secondary to heatstroke have not been reported in dogs.…”
Section: Introductionmentioning
confidence: 99%